1988
DOI: 10.2307/3350034
|View full text |Cite
|
Sign up to set email alerts
|

The Past and Future of Home- and Community-Based Long-Term Care

Abstract: For almost three decades researchers have sought to quantify the benefits of home and community care for the elderly, invariably assuming that such care would be an economical substitute for institutionalization. Twenty-seven studies that met rigorous criteria of design, size, and subject were analyzed and the results were synthesized to address the effects on institutional utilization and expenditures, and patient health status and well-being. Home- and community-based health care services are shown to raise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(108 citation statements)
references
References 0 publications
3
104
1
Order By: Relevance
“…A "woodwork effect" occurs if individuals who need services take advantage of HCBS waivers when they would not be willing to use equivalent institutional services. The early demonstration studies found that HCBS programs were associated with benefits but they increased costs because many participants who used HCBS would not have entered a nursing home (Kemper, Applebaum, & Harrigan, 1987;Weissert, Cready, & Pawelak, 1988;Weissert & Hedrick, 1994). A review of more recent demonstrations by Grabowski (2006) also found that HCBS programs generally had problems targeting services to those who would have otherwise used institutional care and were associated with increased costs.…”
Section: Introductionmentioning
confidence: 90%
“…A "woodwork effect" occurs if individuals who need services take advantage of HCBS waivers when they would not be willing to use equivalent institutional services. The early demonstration studies found that HCBS programs were associated with benefits but they increased costs because many participants who used HCBS would not have entered a nursing home (Kemper, Applebaum, & Harrigan, 1987;Weissert, Cready, & Pawelak, 1988;Weissert & Hedrick, 1994). A review of more recent demonstrations by Grabowski (2006) also found that HCBS programs generally had problems targeting services to those who would have otherwise used institutional care and were associated with increased costs.…”
Section: Introductionmentioning
confidence: 90%
“…Although there is some possibility of substitution from informal (Van Houtven and Norton, 2004) and formal (Nyman et al, 1997) care sources, nursing homes are the destination of last resort for many individuals, implying that demand is quite inelastic. Individuals generally prefer long-term care in the least restrictive setting possible (Kane and Kane, 2001), and the empirical evidence is suggestive of greater demand responsiveness among nursing home substitutes such as home health care (Lee et al, 1999) or community-based services (Weissert et al, 1988). Similarly, a preference for care from family members and friends has also been offered as a potential explanation for the limited growth of the private long-term care insurance market (Pauly, 1990).…”
Section: Moral Hazard and Nursing Home Utilization: Conceptual Frameworkmentioning
confidence: 97%
“…Several studies show that informal care and in-patient care are substitutes (see e.g. [5,6,9,12,17,23,25,35,37,40]). Testing for the IIA property in our data reveals that an application of the MNL would result in biased estimates.…”
Section: Modelmentioning
confidence: 99%